Should theology take evolutionary ethics seriously? A conversation with Hannah Arendt and Maxine Sheets-Johnstone - Van Huyssteen, Wentzel (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
In this essay I attempt to bridge the gap between evolutionary and theological meta-narratives by making a proposal for a bottom-up, contextual form of evolutionary ethics, and then specifically ask how this might apply to the evolution of morality, to ethical judgments, and the status of ethical judgments and moral codes in theology. Most importantly, this will imply a christian ethics, and a notion of morality that proceed not from a consideration of rules, duties, rights, moral judgments, moral status, but proceeds rather, from the examination of the fundamental evolutionary realities of human nature. This argument is developed against the background of an analysis of Maxine Sheets-Johnstone’s engagement with the work of Hannah Arendt on the notion of evil. Finally I argue that the work of evolutionary ethicists are of great importance for theologians because of their direct interest in how the evolutionary origins of human behaviour is to be explained, and in which way our behaviour has been constrained, but not determined, by biological factors. Evolution by natural selection can explain our tendency to think in normative terms, i.e., our innate sense of moral awareness. However, evolutionary explanations of this moral awareness cannot explain our moral judgments, nor justify the truth claims of any of our moral judgments. Why and how we make moral judgments can only be explained on the level of cultural evolution, and by taking into account the historical embeddedness of our moral codes in religious and political conventions. For Christian Theology the choice will not be between a moral vision that is inherent in revelation and is, therefore, ‘received’ and not invented or constructed. Instead, on a post-Foundational view our moral codes and ethical convictions of what is ‘received’ is itself an interpretative enterprise, shaped experientially through our embeddedness in communities and cultures.